Reproductive performance of prepubertal yearling Bos indicus heifers submitted to programs for induction of ovulation prior to a timed-artificial insemination protocol - Lopes, Ana Luiza Müller (2025)
In beef production systems in Brazil based mainly on the Nelore breed, there has been a significant increase in the use of young heifers aged 14-16 mo old. This scenario has led to the development of strategies aimed at advancing puberty and first calving, intending to prolong the productive life of females and maximize the economic benefits of these systems. Therefore, the present study aimed to evaluate the effects of two ovulation induction protocols prior to the first timed-artificial insemination (TAI) protocol in prepubertal Nelore heifers (Bos indicus). A total of 2,000 heifers were randomly assigned to two treatments: P4+E2 (intravaginal progesterone [P4] device followed by estradiol [E2] cypionate) and iP4 (long- acting injectable P4). Reproductive variables analyzed included the presence of a corpus luteum (CL), uterine diameter, expression of estrus, pregnancy per AI (P/AI) and pregnancy loss. The results showed that more heifers in the P4+E2 group had CL at the start of the TAI protocol, estrus before AI, and better P/AI at 40 and 120 d compared to heifers receiving iP4 alone. Although treatment did not affect pregnancy loss, CL at the start of the protocol was associated with greater expression of estrus and P/AI regardless of treatment. Similarly, heifers expressing estrus had greater P/AI, again regardless of treatment. Incidence of CL at the start of the TAI protocol and P/AI at 120 d was higher in heifers of intermediate and older age, while pregnancy loss was higher in younger heifers. Heifers with higher body weight or body weight daily gain had better reproductive performance with higher incidence of CL, more estrus, and higher P/AI. In conclusion, ovulation induction protocols combining P4 plus E2 are more effective in inducing ovulation and improving reproductive performance in prepubertal yearling Nelore heifers.